Coastal geomorphological perspectives on deep blue carbon accumulation and its spatial distribution in a tropical small island mangrove ecosystem - Askiyamin Alimuddin; Bachtiar W. Mutaqin; Muhammad Kamal (Wetlands Ecology and Management, 2026)

Synergistic Effects of Shewanella algae A3 and Serratia marcescens Van80 UB3 on Immune Response, Gene Expression and Resistance to Vibrio parahaemolyticus Vp5 in Pacific White Shrimp - Sutanti Sutanti; Sukenda Sukenda; Widanarni Widanarni; Alimuddin Alimuddin; Ratu Siti Aliah; Handang Widantara; Dendi Hidayatullah (Journal of Fish Diseases, 2026)
This study addresses the infection caused by Vibrio parahaemolyticus Vp5, which carries the pir A and pirB toxin genes responsible for hepatopancreatic necrosis disease (AHPND) in Pacific white shrimp, leading to significant production losses. The use of a host‐associated probiotic is considered a promising strategy to prevent such diseases. In this laboratory experiment, the effect of indigenous probiotics Shewanella algae A3 and Serratia marcescens Van80 UB3 was evaluated in terms of histopathology, immunity, gene expression and their protective ability against AHPND‐causing bacteria in Pacific white shrimp (2 ± 0.5 g) over a 30‐day feeding trial. A total of 150 shrimp of post larvae‐10 (PL‐10) were divided into five treatment groups: probiotic A ( S. algae A3) at 10 6 cfu/g, probiotic B ( S. marcescens Van80 UB3) at the same dose, probiotic C (a 1:1 mixture of both strains), a positive control K (+) (standard feed with infection) and negative control K (−) (standard feed without infection). After a 30‐day feeding, the shrimp were challenged with V. parahaemolyticus Vp5 and survival was recorded for 14 days. The result showed that shrimp treated with the mixed probiotic (group C) had the highest survival (95.83% ± 1.44%), which was significantly higher than the positive control (72.22% ± 1.57%) ( p proPO and serine protease in the intestine, muscle and hepatopancreas was significantly increased in the mixed probiotic group compared to the other treatments. In contrast, the expression of the cathepsin L gene, associated with muscle growth, was significantly lower in this group ( p S. algae A3 and S. marcescens Van80 UB3 at 10 6 cfu/g of feed is effective in improving shrimp health and resistance to AHPND.

Reproductive responses of Synodontis eupterus to different dietary melatonin levels under blue light conditions - Agus Oman Sudrajat; Shofihar Sinansari; Harton Arfah; Eni Kusrini; Bastiar Nur; Darmawan Setia Budi; Odang Carman; Alimuddin Alimuddin (Animal Reproduction Science, 2026)

Upcycling eucalyptus kraft lignin into fluorescent graphene quantum dots for reproductive cell imaging in aquaculture biotechnology - Anna Octavera; Harits Atika Ariyanta; Khanesisya Luthfiyah Zahra; Diana Faoziah Hakim; Fajar Maulana; Novia Amalia Sholeha; Dian Hardiantho; Nurlatiha Khairun Nisa; Widya Fatriasari; Alimuddin (Bioresource Technology, 2026)

Efficacy of an inactivated polyvalent Edwardsiella ictaluri vaccine with booster in enhancing immune response and protection in striped catfish (Pangasianodon hypophthalmus) - Uni Purwaningsih; Sukenda Sukenda; Angela Mariana Lusiastuti; Alimuddin Alimuddin; Widanarni Widanarni; Sri Nuryati; Dendi Hidayatullah (Aquaculture International, 2026)

Dietary Banana Stem Powder Enhances Immune Response, Disease Resistance, and Growth in Pacific White Shrimp Under AHPND Challenge - Sri Nuryati; Anna Octavera; Salma Nur Karima; Alimuddin; Munti Yuhana; Sukenda (Thalassas: An International Journal of Marine Sciences, 2025)

Dietary crude protein requirement of golden rabbitfish Siganus guttatus fed low fishmeal diets with varying soybean meal: influence on growth, plasma biochemistry, amino acid profiles, and IGF-1 mRNA expression - Asda Laining; Sri Redjeki Hesti Mulyaningrum; Bunga Rante Tampangallo; Ike Trismawanti; Muhammad Chaidir Undu; Alimuddin Alimuddin; Igor Pirozzi (Aquaculture International, 2025)

Recent Advances in the Third Order Nonlinear Optical Properties of Chalcone Derivatives: a Review - Mohd Abdul Mujeeb; Md. Shahbaz; Md. Zafer Alam; Rizwan ul Haq Ansari; H. Aleem Basha; Alimuddin; Salman A. Khan (Journal of Fluorescence, 2025)

A Review of the Recent Advances of Carbon Dots in the Application of Photocatalytic Degradation of Methylene Blue Dye and their Future Prospects - Alimuddin (Journal of Fluorescence, 2025)

Assessment of seasonal variations in antibiotic resistance genes and microbial communities in sewage treatment plants for public health monitoring - Abhishek Keer; Yukti Oza; Dattatray Mongad; Dinesh Ramakrishnan; Dhiraj Dhotre; Abdelfattah Ahmed; Alimuddin Zumla; Yogesh Shouche; Avinash Sharma (Environmental Pollution, 2025)

Indigenous Gram-Negative Bacteria as Probiotics for Pacific White Shrimp (Litopenaeus vannamei) - Sutanti Sutanti; Sukenda Sukenda; Widanarni Widanarni; Alimuddin Alimuddin; Ratu Siti Aliah; Arif Rahmat Ardiansyah; Ekky Ilham Romadhona (Current Microbiology, 2025)

Multi-Step Synthesis, Characterization and Physicochemical Investigation of Benzylated Indole Thiosemicarbazone as Selective Switch on Sensing Properties for Copper Ion - Md. Zafer Alam; Suhail Ahmad; Md. Mohasin; Umme Salma; Alimuddin; Humaira Parveen; Sayeed Mukhtar; Salman A. Khan (Journal of Fluorescence, 2025)

Effectiveness of the Edwardsiella ictaluri whole-cell vaccine in controlling enteric septicemia of catfish disease in striped catfish (Pangasianodon hypophthalmus) - Uni Purwaningsih; Sukenda Sukenda; Angela Mariana Lusiastuti; Alimuddin Alimuddin; Widanarni Widanarni; Sri Nuryati (Aquaculture International, 2025)

A Comprehensive Review on Plant-Based Medications and Chemical Approaches for Autism Spectrum Disorders (ASDs) Psychopharmacotherapy - Vrish Dhwaj Ashwlayan; Ratneshwar Kumar Ratnesh; Divya Sharma; Alok Sharma; Akansha Sangal; Alimuddin Saifi; Jay Singh (Indian Journal of Microbiology, 2025)

Fluorescent/ Photoluminescent Carbon Dots as a Sensor for the Selective and Sensitive Detection of Fe3+/Fe2+ Metal Ions. A Review of the Last Decade - Md. Shahbaz; Umme Salma; Md. Zafar Alam; Mohd Abdul Mujeeb; Rizwan ul Haq Ansari; H. Aleem Basha; Alimuddin; Salman A. Khan (Journal of Fluorescence, 2025)

High Inhibition Activity of CQDs-Macaranga tanarius Organic Framework Nanomaterial-Based Antibacterials - Saparuddin Saparuddin; Djunarlin Tojang; Alimuddin Alimuddin; Zul Arham (Indian Journal of Microbiology, 2024)

Improving reproductive performance and larvae survival by dietary administration of probiotic Bacillus cereus NP5 in female African catfish Clarias gariepinus - Valensia Enzeline; Widanarni Widanarni; Agus Oman Sudrajat; Alimuddin Alimuddin; Hasan Nasrullah (Aquaculture International, 2024)

Novel indigenous probiotic isolated from the healthy Pacific white shrimp Litopenaeus vannamei intestine in differing stages based on metagenomic and screening approaches - Sutanti Sutanti; Sukenda Sukenda; Widanarni Widanarni; Alimuddin Alimuddin; Ratu Siti Aliah (Fish & Shellfish Immunology, 2024)

Structure and Diversity of Microbiomes Associated with the Gastrointestinal Tracts of Wild Spiny Lobsters and Profiling Their Potential Probiotic Properties Using eDNA Metabarcoding - Muhamad Amin; Hussein Taha; Laila Musdalifah; Muhamad Ali; Alimuddin Alimuddin; Sahrul Alim; Takaomi Arai (Fishes, 2024)
Microbial communities have been documented as playing many pivotal roles, and contributing to the growth or health performance of animal hosts. Thus, many studies are currently looking for potential beneficial bacteria “probiotics” from diverse environments, including wild species. The present study aimed to investigate the diversity and potential metabolic functions of bacterial communities in the gastrointestinal tract of wild spiny lobsters. The gastrointestinal (GI) tracts of two wild lobster species (Panulirus ornatus and Panulirus homarus) were dissected aseptically and analyzed through high-throughput sequencing, followed by PICRUSt analysis. The results exposed that the most dominant phyla inhabiting both lobster species at the post-puerulus and juvenile stages were Proteobacteria, Firmicutes, Bacteriodota, Patescibacteria, and Verrucomicrobiota, while at the genus level, the GI tracts were mostly dominated by Photobacterium, Candidatus Bacillopora, Vibrio, and Catenococcus at the post-peurulus stage, and Vibrio, Catenococcus, Acanthopleuribacter, Acinetobacter, Pseudoalteromonas, Grimontia, and Photobacterium at the juvenile stage. Further metagenomic prediction analysis discovers many potential probiont properties indicated by the detection of marker genes corresponding to many important metabolic activities, such as antimicrobial compounds (streptomycin, vancomycin, carbapenem, tetracycline, novobiocin, penicillin, cephalosporin, ansamycines, butirosin, and neomycin), antioxidants (e.g., flavonoids and carotenoids), and several important digestive enzymes (e.g., lipase, protease, and amylase). These results suggest that GI tracts of wild spiny lobsters are potential sources to discover novel probionts for aquaculture purposes. Further studies, such as the isolation of the natural product-producing bacteria, or cloning of the beneficial compound-identified genes, are highly recommended to develop novel probiotic strains for aquaculture purposes.

Microbial diversity associated with the natural spring water of Western Himalayas - Yukti Oza; Mrunal Karande; Rochita Ghosh; Janhvi Mishra Rawat; Sumit Purohit; Balwant Rawat; Alimuddin Zumla; Avinash Sharma (Vegetos, 2024)

Variability in plasma rifampicin concentrations and role of SLCO1B1 , ABCB1 , AADAC2 and CES2 genotypes in Ethiopian patients with tuberculosis - Tesemma Sileshi; Eyasu Makonnen; Nigus Fikrie Telele; Victoria Barclay; Alimuddin Zumla; Eleni Aklillu (Infectious Diseases, 2024)

Synthesis of Fluorescent Pyrazoline Sensors as Versatile Tool for Zinc ion Detection: A Mini-Review - Md. Zafer Alam; Suhail Ahmad; Alimuddin; Salman A. Khan (Journal of Fluorescence, 2024)

Examining the microbial composition of natural springs in Bhaderwah, Jammu and Kashmir, India - Abhishek Gupta; Vandana Dutt; Neeraj Sharma; Swapnil Kajale; Arun Bhatt; Shuja Shafi; Esam Azhar; Alimuddin Zumla; Avinash Sharma (Environmental Monitoring and Assessment, 2023)

A Review on Schiff Base as a Versatile Fluorescent Chemo-sensors Tool for Detection of Cu2+ and Fe3+ Metal Ion - Md Zafer Alam; Alimuddin; Salman A. Khan (Journal of Fluorescence, 2023)

High carbohydrate increases amylase, plasma glucose, and gene expression related to glycolysis in giant gourami Osphronemus goramy - Dian Novita Sari; Julie Ekasari; Hasan Nasrullah; Muhammad Agus Suprayudi; Alimuddin Alimuddin (Fish Physiology and Biochemistry, 2022)

Early immune gene development and expression in African catfish Clarias gariepinus after challenged with Aeromonas hydrophila - Hasan Nasrullah; Dwi Hany Yanti; Nurly Faridah; Dian Hardiantho; Yanti Inneke Nababan; Sukenda Sukenda; Alimuddin Alimuddin (Aquaculture International, 2021)

Development of primary cell culture from spleen of giant gourami Osphronemus goramy for propagation of giant gourami iridovirus (GGIV) - Lila Gardenia; Sukenda Sukenda; Muhammad Zairin Junior; Angela Lusiastuti; Alimuddin Alimuddin (Journal of Fish Diseases, 2020)
The severe mortality of fish due to the infection of megalocytivirus caused significant economic losses. Since 2011, megalocytivirus (giant gourami iridovirus (GGIV)) has become the main pathogen in giant gourami ( Osphronemus goramy ), particularly in West Java, Central Java and Bali. This study aimed to develop primary cell culture from spleen as the target organ for propagating megalocytivirus in vitro, which was developed by explant method with enzymatic dissociation. Optimization was carried out at incubation temperature, medium and serum concentrations. The origin of the primary cell, cell susceptibility and GGIV pathogenicity were observed. The results showed that the primary cell (GP cells) can grow well in 10% foetal bovine serum L‐15 medium at 27°C, which was sufficient for cell growth. PCR and BLAST analyses showed the primary cell was originated from giant gourami. In infected GP cells, cell enlargement and cell rounding were observed. Virus propagated in GP cells was highly virulent when injecting giant gourami in an artificial infection experiment. Intraperitoneal injection of diluted virus supernatant showed 100% mortality in 7–11 days post‐injection and 97% mortality in 21 days post‐cohabitation, with abnormalities observed in spleen and kidney. In conclusion, GP cell was successfully subcultured for more than 30 passages and susceptible to GGIV.

Immunometabolism: new insights and lessons from antigen-directed cellular immune responses - Renata Ramalho; Martin Rao; Chao Zhang; Chiara Agrati; Giuseppe Ippolito; Fu-Sheng Wang; Alimuddin Zumla; Markus Maeurer (Seminars in Immunopathology, 2020)

Identification of giant gourami iridovirus (GGIV): a new infectious spleen and kidney necrosis virus (ISKNV) from natural outbreak in cultured Osphronemus goramy - Sukenda Sukenda; Lila Gardenia; M. Zairin; Angela Lusiastuti; Alimuddin Alimudin (Aquaculture International, 2020)

Antimicrobial properties against Aeromonas hydrophila and immunostimulant effect on Clarias gariepinus of Piper betle, Psidium guajava, and Tithonia diversifolia plants - Nunak Nafiqoh; Sukenda; M. Zairin; Alimuddin; Angela Lusiastuti; Samira Sarter; Domenico Caruso; Jean-Christophe Avarre (Aquaculture International, 2020)

Immune response and resistance of Pacific white shrimp larvae administered probiotic, prebiotic, and synbiotic through the bio-encapsulation of Artemia sp. - Hamsah Hamsah; Widanarni Widanarni; Alimuddin Alimuddin; Munti Yuhana; Muhammad Zairin Junior; Dendi Hidayatullah (Aquaculture International, 2019)

Identification of M2 macrophages in anterior pituitary glands of normal rats and rats with estrogen-induced prolactinoma - Ken Fujiwara; Megumi Yatabe; Alimuddin Tofrizal; Depicha Jindatip; Takashi Yashiro; Ryozo Nagai (Cell and Tissue Research, 2017)

Expression of the heparin-binding growth factor midkine and its receptor, Ptprz1, in adult rat pituitary - Ken Fujiwara; Kotaro Horiguchi; Rita Maliza; Alimuddin Tofrizal; Khongorzul Batchuluun; Dini Ramadhani; Rahimi Syaidah; Takehiro Tsukada; Morio Azuma; Motoshi Kikuchi; Takashi Yashiro (Cell and Tissue Research, 2015)

In situ hybridization analysis of the temporospatial expression of the midkine/pleiotrophin family in rat embryonic pituitary gland - Ken Fujiwara; Rita Maliza; Alimuddin Tofrizal; Khongorzul Batchuluun; Dini Ramadhani; Takehiro Tsukada; Morio Azuma; Kotaro Horiguchi; Motoshi Kikuchi; Takashi Yashiro (Cell and Tissue Research, 2014)

Intraperitoneal Germ Cell Transplantation in the Nile Tilapia Oreochromis niloticus - Rodolfo Farlora; Shoko Hattori-Ihara; Yukata Takeuchi; Makoto Hayashi; Anna Octavera; Alimuddin; Goro Yoshizaki (Marine Biotechnology, 2014)

Tropical forest mapping using a combination of optical and microwave data of ALOS - Nguyen Thanh Hoan; Ryutaro Tateishi; Bayan Alsaaideh; Thomas Ngigi; Ilham Alimuddin; Brian Johnson (International Journal of Remote Sensing, 2013)

Cloning and nutritional regulation of polyunsaturated fatty acid desaturase and elongase of a marine teleost, the nibe croaker Nibea mitsukurii - Yoji Yamamoto; Naoki Kabeya; Yutaka Takeuchi; Alimuddin; Yutaka Haga; Shuichi Satoh; Toshio Takeuchi; Goro Yoshizaki (Fisheries Science, 2010)

Expression of Masu Salmon Δ5-Desaturase-Like Gene Elevated EPA and DHA Biosynthesis in Zebrafish - Alimuddin; Goro Yoshizaki; Viswanath Kiron; Shuichi Satoh; Toshio Takeuchi (Marine Biotechnology, 2007)

Enhancement of EPA and DHA biosynthesis by over-expression of masu salmon Δ6-desaturase-like gene in zebrafish - Alimuddin; Goro Yoshizaki; Viswanath Kiron; Shuichi Satoh; Toshio Takeuchi (Transgenic Research, 2005)